1998
DOI: 10.1002/(sici)1097-0215(19981109)78:4<491::aid-ijc16>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of gap junctional intercellular communication by perfluorinated fatty acids is dependent on the chain length of the fluorinated tail

Abstract: Perfluorinated fatty acids (PFFAs), such as perfluorooctanoic acid (PFOA) and perfluorodecanoic acid (PFDA), are known peroxisome proliferators and hepatocarcinogens. A causal link between an increase in the oxidative stress by peroxisomes and tumor promotion has been proposed to explain the hepatocarcinogenicity of PFOA and PFDA. However, the down-regulation of gap junctional intercellular communication (GJIC) has also been linked to the tumorpromoting properties of many carcinogens. Therefore, the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
1
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(117 citation statements)
references
References 13 publications
6
105
1
4
Order By: Relevance
“…When compared on an average daily intake (ADI) basis, PFBS is at least 150-fold less toxic than PFOS. The difference in toxicity between PFBS and PFOS observed in the avian studies is not unexpected as the toxicity of PFAAs has been shown to be related to the number of perfluoroalkyl carbons (Goecke-Flora and Reo 1996;Upham et al 1998;Hu et al 2002;Martin et al 2003a). For instance, while gap junction communication (GJIC) was inhibited in liver epithelial cells (WB-F344) exposed to PFOS (eight perfluorinated carbons), it was not inhibited by PFAAs with carbon chain lengths of less than five or more than 16.…”
Section: Discussionmentioning
confidence: 93%
“…When compared on an average daily intake (ADI) basis, PFBS is at least 150-fold less toxic than PFOS. The difference in toxicity between PFBS and PFOS observed in the avian studies is not unexpected as the toxicity of PFAAs has been shown to be related to the number of perfluoroalkyl carbons (Goecke-Flora and Reo 1996;Upham et al 1998;Hu et al 2002;Martin et al 2003a). For instance, while gap junction communication (GJIC) was inhibited in liver epithelial cells (WB-F344) exposed to PFOS (eight perfluorinated carbons), it was not inhibited by PFAAs with carbon chain lengths of less than five or more than 16.…”
Section: Discussionmentioning
confidence: 93%
“…Upham et al (33) found that only PFCAs with chain lengths of 7-10 C inhibited gap junction intercellular communication in rat liver epithelial cells. Furthermore, the degree of inhibition increased with increasing chain length (33).…”
Section: Resultsmentioning
confidence: 99%
“…Gap junctions have also gained attention for a phenomenon called the radiation-induced bystander effect, in which non-irradiated cells exhibit similar effects to irradiated cells as a result of signals received from nearby irradiated cells via gap junctions (Azzam et al, 2004;Azzam and Little, 2004;Mitchell et al, 2004b;Mitchell et al, 2004a). In this process, gap junctional intercellular communication may also be involved in a range of cellular stress responses including ionizing radiation and oxidative stress (Upham et al, 1998), UV radiation (Provost et al, 2003) and HS (Hamada et al, 2003). Thus, between cells in close proximity, gap junctions may have an important role in the exchange of signaling molecules for proteostasis communication.…”
Section: Reviewmentioning
confidence: 99%